2021
DOI: 10.1111/are.15206
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide induced unfolded protein response and related anti‐lipopolysaccharide factor expression in Pacific white shrimp, Litopenaeus vannamei

Abstract: Litopenaeus vannamei (L. vannamei), also known as Pacific white shrimp, is one of the largest cultured shrimp species in the world, accounting for more than 70 per cent of global shrimp production for its rapid growth, tender meat and high nutritional value (Loker et al., 2010). Unfortunately, L. vannamei is susceptible to bacteria which can lead to massive death of shrimp, and cause huge economic losses to the farming industry (Walker & Winton, 2010). Therefore, it is necessary to properly understand the path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have found environmental stress could induce ER stress ( Liang et al, 2016 ). However, most research mainly focused on unfolded protein response pathway ( Chen et al, 2012 ; Yuan et al, 2017 ; Xu et al, 2018 ; Qu et al, 2021 ), whereas the response of ERAD to environmental stress was rarely reported. In this study, the analysis of KEGG pathway revealed that 18 genes were significantly up-regulated after MC-LR exposure for 72 h, among which Npl4 and RAD23A played an important role in substrate transfer from ER to proteasome.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found environmental stress could induce ER stress ( Liang et al, 2016 ). However, most research mainly focused on unfolded protein response pathway ( Chen et al, 2012 ; Yuan et al, 2017 ; Xu et al, 2018 ; Qu et al, 2021 ), whereas the response of ERAD to environmental stress was rarely reported. In this study, the analysis of KEGG pathway revealed that 18 genes were significantly up-regulated after MC-LR exposure for 72 h, among which Npl4 and RAD23A played an important role in substrate transfer from ER to proteasome.…”
Section: Discussionmentioning
confidence: 99%